COVID-19, DOMESTIC VIOLENCE AND GENDER - Ikhwanuddin Harahap (IAIN Padangsidimpuan, 2021)
Ideally, home is the safest place for household members. But in fact, the house can be “the hell” for family members. Covid-19 has impact on the harmony of the family, especially husband and wife. They stay at home during Covid-19 for a long time. In fact, living together create the new problem, namely domestic violence. This study tent to investigate the domestic violence during Covid-19 and analyze it from gender perspective. It can be seen that the domestic violence was increasing during Covid-19, where wives were victims. Wives have double burden in home.